Contending Views and Power Struggle within Islam: The Clash of Religious Discourse and Citizenship in Contemporary Indonesia - Makhasin, Luthfi; Sugiarto, Bowo (Political Science Program, Universitas Negeri Semarang, 2020)
In the last 20 years, the ‘conservative turn’ toward overtly Islamic identity in Indonesia paved the way for raising political Islamism. This political Islamism aspires to the continuing Islamization, implementation of sharia, and even the establishment of a global caliphate. Emerging Islamist forces such as Front Pembela Islam, Jemaah Tarbiyah, and Hizbut Tahrir Indonesia along with the conservative turn, therefore, pose the normative-political challenges to both republican and liberal notions of citizenship. This paper deals with the question of religion and citizenship under the democratic space in contemporary Indonesia. By examining three variants of Islamic citizenship, religion vigilant, pragmatic, and rejectionist citizenship, this paper tries to address the following question: to what extent Islamism challenges the discourse of citizenship in contemporary Indonesia? We argue that while Islamism apparently rises and gains followers, the state and mainstream Muslim organizations (Nahdlatul Ulama and Muhammadiyah), and their emphasis on Pancasila and commitment to NKRI successfully manage to reconcile Islam and citizenship under democratic space.